PRECISE-FERTILIZATION AS AN ADDED VALUE FOR FARM PRODUCTS BY INCREASING GLOBAL AWARENESS ON HEALTH AND ENVIRONMENTAL EFFECTS - Sulis Dyah Candra; Ketut Anom Wijaya (UPT Penerbitan Universitas Jember, 2012)
Intensive nutrient managements for crop production are one of agriculture management strategies that are not yet widely adopted in most third world countries.Precise N Fertilization as a part of intensive nutrient managements is a great way tomanage input efficiency; yet, the technology is feasible enough for farmers to apply, inorder to increase the farm product quality while improve access in modern market.Nitrogen (N) required for plant growth and development in large numbers, but the plant isonly capable of absorbing an average of less than 50% N provided through conventionalfertilization. Greenhouse gases emissions are increasing mostly because of expanding useof N fertilizers, while the carcinogenic effect of N residue on farm products is a dangerousrisk for human health. By increasing the awareness on health and environmental effects forfarm products especially concerning precise N fertilization, consumer will get healthbenefit while producer will get an added value for their products. Thus, by applying betterinput efficiency farmers could simultaneously increase the price while meeting the higherconsumer demands even with gradually stricter standards in term of farm product qualityand market requirements.